DOI: 10.11606/d.10.2019.tde-28092018-151743
|View full text |Cite
|
Sign up to set email alerts
|

<b>Estado oxidativo de neonatos e fêmeas caninas no periparto vaginal eutócico ou cesariana eletiva</b>

Abstract: AGRADECIMENTOS "É preciso que eu suporte duas ou três larvas se eu quiser conhecer as borboletas. Dizem que são tão belas. " Antoine de Saint-Exupéry, -Le Petit Prince À toda minha família e amigos (Flavinha, Gabi, Jé, Ju e Lu) por sempre acreditarem em mim e na minha capacidade. Especialmente à minha mãe, agradeço pelo amor infinito e presença em todas as etapas da minha vida. Não existe no mundo palavras suficientes para agradecer o seu constante apoio em absolutamente tudo o que eu faço, por me ensinar diar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Regardless of delivery method, the RR of cats was higher than that of dogs. 12,16,20,29 While an average RR of up to 40 movements per min (mpm) is expected in newborn dogs, 12,30 in newborn cats in this study, averages above 100 mpm were observed. It is possible that cats demonstrate greater maturity of the adaptive breathing reflex, carotid chemoreceptors or lung structures than dogs, or a greater expansion of the chest wall, to compensate for hypoxemia during parturition.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Regardless of delivery method, the RR of cats was higher than that of dogs. 12,16,20,29 While an average RR of up to 40 movements per min (mpm) is expected in newborn dogs, 12,30 in newborn cats in this study, averages above 100 mpm were observed. It is possible that cats demonstrate greater maturity of the adaptive breathing reflex, carotid chemoreceptors or lung structures than dogs, or a greater expansion of the chest wall, to compensate for hypoxemia during parturition.…”
Section: Discussionmentioning
confidence: 48%
“…However, further studies are needed to examine cardiorespiratory maturity in newborn cats compared with dogs. In cats, a higher SpO 2 than that in dogs 29,31 was observed in both groups, possibly due to their higher RR and HR.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A lower concentration of total, direct, and indirect bilirubin were observed in the mules when compared to horses. In horse neonates, a physiological increase in indirect bilirubin during the first week of life has been reported, probably due to a rapid rate of the recurrence of fetal red blood cells [16,23,24]. However, studies have reported an antioxidant role of bilirubin in human serum, protecting cell membranes from lipid peroxidation due to its lipophilic properties [25].…”
Section: Discussionmentioning
confidence: 99%
“…This accelerated adjustment could be attributed to their enhanced resilience and cognitive capabilities, possibly from genetic heterosis [23,26,27]. As a result, mule neonates tend to demonstrate a faster adaptation to their surroundings when compared to their horse counterparts [16,24].…”
Section: Discussionmentioning
confidence: 99%